Characterization of glycolytic enzymes and pyruvate kinase M2 in Type 1 and 2 diabetic nephropathy - Gordin, Daniel; Kannt, Aimo (Diabetes care, 2019)
OBJECTIVE Elevated glycolytic enzymes in renal glomeruli correlated with preservation of renal function in the Medalist Study, individuals with ≥50 years of type 1 diabetes. Specifically, pyruvate kinase M2 (PKM2) activation protected insulin-deficient diabetic mice from hyperglycemia-induced glomerular pathology. This study aims to extend these findings in a separate cohort of individuals with type 1 and type 2 diabetes and discover new circulatory biomarkers for renal protection through proteomics and metabolomics of Medalists’ plasma. We hypothesize that increased glycolytic flux and improved mitochondrial biogenesis will halt the progression of diabetic nephropathy. RESEARCH DESIGN AND METHODS Immunoblots analyzed selected glycolytic and mitochondrial enzymes in postmortem glomeruli of non-Medalists with type 1 diabetes (n = 15), type 2 diabetes (n = 19), and no diabetes (n = 5). Plasma proteomic (SOMAscan) (n = 180) and metabolomic screens (n = 214) of Medalists with and without stage 3b chronic kidney disease (CKD) were conducted and significant markers validated by ELISA. RESULTS Glycolytic (PKM1, PKM2, and ENO1) and mitochondrial (MTCO2) enzymes were significantly elevated in glomeruli of CKD− versus CKD+ individuals with type 2 diabetes. Medalists’ plasma PKM2 correlated with estimated glomerular filtration rate (r2 = 0.077; P = 0.0002). Several glucose and mitochondrial enzymes in circulation were upregulated with corresponding downregulation of toxic metabolites in CKD-protected Medalists. Amyloid precursor protein was also significantly upregulated, tumor necrosis factor receptors downregulated, and both confirmed by ELISA. CONCLUSIONS Elevation of enzymes involved in the metabolism of intracellular free glucose and its metabolites in renal glomeruli is connected to preserving kidney function in both type 1 and type 2 diabetes. The renal profile of elevated glycolytic enzymes and reduced toxic glucose metabolites is reflected in the circulation, supporting their use as biomarkers for endogenous renal protective factors in people with diabetes.
Gesehen am 22.10.2019